The effect of left-right reversal on film: Watching Kurosawa reversed - Bertamini, Marco (Pion, 2011)
The mirror reversal of an image is subtly different from the original. Often such change goes unnoticed in pictures, although it can affect preference. For the first time we studied the effect of mirror reversal of feature films. People watched Yojimbo or Sanjuro in a cinema, both classic films by Akira Kurosawa. They knew that this was a study and filled out a questionnaire. On one day Yojimbo was shown in its original orientation, and on another day the film was mirror reversed. Sanjuro was shown reversed on one day and non-reversed on another day. Viewers did not notice the reversal, even when they had seen the film before and considered themselves fans of Kurosawa. We compared this with estimates from a survey. In addition, the question about the use of space (scenography) revealed that although people who had seen the film before gave higher ratings compared with those who had not, this was only true when the film was not reversed.